2012
DOI: 10.4103/0974-2700.93107
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of ultrasound-guided nerve block for management of limb injuries by emergency care physicians

Abstract: Background:Patients require procedural sedation and analgesia (PSA) for the treatment of acute traumatic injuries. PSA has complications. Ultrasound (US) guided peripheral nerve block is a safe alternative.Aim:Ultrasound guided nerve blocks for management of traumatic limb emergencies in Emergency Department (ED).Setting and Design:Prospective observational study conducted in ED.Materials and Methods:Patients above five years requiring analgesia for management of limb emergencies were recruited. Emergency Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…In recent years, ultrasound technology has been applied for nerve block techniques [12]. Thallaj et al [13] reported high success rates, good anesthesia effects, and high patient satisfaction with ultrasound-guided obturator nerve block, and Bhoi et al [14] achieved satisfactory effects with ultrasoundguided nerve block for limb trauma in emergency patients. Thomas et al [15] showed that the ultrasound-guided interscalene brachial plexus block was safe and effective and that the time to onset of the sensory and motor block was shorter than that in blocks performed using a nerve stimulator.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ultrasound technology has been applied for nerve block techniques [12]. Thallaj et al [13] reported high success rates, good anesthesia effects, and high patient satisfaction with ultrasound-guided obturator nerve block, and Bhoi et al [14] achieved satisfactory effects with ultrasoundguided nerve block for limb trauma in emergency patients. Thomas et al [15] showed that the ultrasound-guided interscalene brachial plexus block was safe and effective and that the time to onset of the sensory and motor block was shorter than that in blocks performed using a nerve stimulator.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methods of analgesia and anesthesia include procedural sedation and regional nerve blocks. Procedural sedation requires monitoring during and after the procedure, places increased demands on staff, has a number of associated risks, increases ED length of stay, and is generally unnecessary for adequate reduction [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
“…There has been an exponential growth in the number of epidural, facet joint and transforaminal injections of the lumbar spine performed by providers not formally trained in anesthesiology [11]. Analyses have focused on complication rates and safety but little is known of the quality of the analgesia following peripheral and neuraxial nerve blockade techniques performed by non-anesthesiologist practitioners [12,13].…”
Section: Introductionmentioning
confidence: 99%